New Treatments And Lt3 (Liothyronine) Combinations / Alternative Therapies (Texas Journal of Medical Science, 2026)
This article reviews new approaches to the treatment of hypothyroidism, specifically the combination of levothyroxine (LT4) and liothyronine (LT3), as well as alternative therapies. The article provides an in-depth review of the limitations of LT4 monotherapy, the rationale for the addition of LT3, clinical trial results, safety issues, and future developments. The aim is to highlight more effective treatment options for patients with persistent symptoms and to emphasize the importance of personalized medicine.